Beyond Financial Inclusion: Digital Transformation and the Redistribution of Prosperity in the Islamic Economy - Marlina Ekawaty; Mochammad Rizki Hanafiansyah (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the development of digital transformation in the Islamic economy over the past decade, its contribution to accelerating prosperity distribution in Indonesia, as well as the opportunities and challenges encountered. Digital transformation has been proven to play a vital role in improving financial inclusion, operational efficiency, and global competitiveness, particularly in Islamic banking, halal industries, zakat management, and mosque transformation. The research employed a systematic literature review of ten scholarly articles related to the digitalization of the Islamic economy. The analysis identified the patterns of development, contributions, opportunities, and challenges highlighted by each study. The findings reveal that digitalization drives economic growth, strengthens zakat redistribution, enhances halal industry competitiveness, and expands the socio-economic role of mosques. However, challenges such as regulatory uncertainty, low digital literacy, and cybersecurity risks remain major barriers. In conclusion, digital transformation serves as both a growth engine and a catalyst for equitable prosperity distribution within the Islamic economy.